Analisis prinsip praktis dari ing ngarsa sung tuladha pada pembelajaran kelas I sekolah dasar - Haffa Islam Mubarok Wiranegara; Joko daryanto (Didaktika Dwija Indria, 2025)
This study aims to examine the implementation of the Ing Ngarsa Sung Tuladha principle as part of the Among System in the learning process of Bahasa Indonesia in first grade at SD Negeri Soropadan. This principle is regarded as a pedagogical foundation that emphasizes the importance of teacher role modeling in shaping students' character and learning behavior, particularly in the early years of primary education. The research employed a qualitative approach using a case study method. Data collection techniques included observation, semi-structured interviews, and documentation. The data were analyzed using a descriptive-analytical approach through Miles and Huberman’s interactive model. The findings reveal that the teacher consistently applied the Ing Ngarsa Sung Tuladha principle across four key dimensions: attitude, behavior, action, and thought. The teacher served not only as a verbal and non-verbal role model but also fostered a learning environment that supports students’ independence, responsibility, and emotional development in a holistic manner. These findings highlight the significance of the teacher’s presence as a figure who internalizes and enacts the values of character education in daily teaching practice.